Magnetic Mineral Diagenesis in a High Temperature and Deep Methanic Zone in Izu Rear Arc Marine Sediments, Northwest Pacific Ocean. Issue 10 (29th October 2018) - Kars, Myriam; Musgrave, Robert J.; Hoshino, Tatsuhiko; Jonas, Ann‐Sophie; Bauersachs, Thorsten; Inagaki, Fumio; Kodama, Kazuto
Abstract: Magnetic mineral diagenesis is an important process in sediments that is responsible for the partial or total destruction of records of Earth's magnetic field variations and also plays an important part in iron and sulfur cycling. A rock magnetic study has been carried out at International Ocean Discovery Program Expedition 350 Site U1437 in the Izu Bonin rear arc to investigate magnetic mineral diagenesis in deeply buried sediments from 775 to 1, 002 m below sea floor (mbsf) with burial temperatures ranging from 67 to 85 °C. Nonsteady state geochemical environments occur within an unusual deep methanic zone (below 850 mbsf) because of a release of sulfate below the shallow sulfate reduction zone. A drastic decline in magnetic susceptibility and remanence is observed at 850 mbsf due to a decrease in ferrimagnetic iron oxide contents. Reduction of (titano)‐magnetite and pyritization occur at this inferred deep sulfate‐methane transition zone. Below 850 mbsf, lower magnetic mineral contents coincide with further methane release. Geochemical analyses support a change in redox conditions and secondary precipitation of iron sulfides and carbonates in the methane‐rich zone. Magnetic mineral alteration is enhanced in zones where methane accumulates underneath low porosity intervals that act as seals. Although geochemical processes due to methane occurrence are likely dominant, more than one mechanism, possibly involving microbial activity, is probably responsible for the observed magnetic mineral assemblage changes. Key Points: Dissolution of magnetic iron oxides is observed in an unusual deep methanic zone Magnetic mineral alteration is enhanced in methane‐rich intervals below lower porosity seal‐like sediments Geochemical reactions involving methane, and possible microbiological processes, are likely responsible for the observed diagenetic alteration